2019
DOI: 10.1007/s10479-019-03256-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-sided assignment games on m-partite graphs

Abstract: We consider a multi-sided assignment game with the following characteristics: (a) the agents are organized in m sectors that are connected by a graph that induces a weighted m-partite graph on the set of agents, (b) a basic coalition is formed by agents from different connected sectors, and (c) the worth of a basic coalition is the addition of the weights of all its pairs that belong to connected sectors. We provide a sufficient condition on the weights to guarantee balancedness of the related multi-sided assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Nevertheless, this property does not extend to the arbitrary multisided markets. Atay and Núñez (2019) recently showed that, in the special case where the market is cycle-free and the valuation function is defined by a specific additivity property, there is for each side an optimal core allocation where all agents of that side achieve their marginal contribution.…”
Section: Matching Markets With Middlemenmentioning
confidence: 99%
“…Nevertheless, this property does not extend to the arbitrary multisided markets. Atay and Núñez (2019) recently showed that, in the special case where the market is cycle-free and the valuation function is defined by a specific additivity property, there is for each side an optimal core allocation where all agents of that side achieve their marginal contribution.…”
Section: Matching Markets With Middlemenmentioning
confidence: 99%